Designing an interactive ice skating dress for young athletes - Häkkilä, J.; Helander, V.; Jamoido, D.; Colley, A. (UbiComp '18 Proceedings of the 2018 ACM International Joint Conference and 2018 International Symposium on Pervasive and Ubiquitous Computing and Wearable Computers, 2018)
Although designing interactive technologies for motivating children to be physically more active has gained much attention, less focus has been directed towards young athletes. Interactive sports garments are an interesting area with much potential from both utilitarian and hedonic design drivers. In this paper, we describe the design process for an interactive skating dress for figure skating. We designed and prototyped an interactive ice skating dress, which detects the spinning movement of the skater, and displays it with changing colors.